Managing interorganisational collaborations to develop medical technologies: the contribution of interpersonal relationships. (18th August 2022) - Olubajo, Linda; Dimitri, Paul; Johnston, Andrew; Owens, Martin
Abstract: The development of medical technologies that effectively meet clinical and patient needs increasingly relies upon collaborative working between clinicians, businesses and universities. While this "open" innovation process may provide access to additional resources, knowledge, and expertise the process is not frictionless. At the personal level, individuals may have different ways of working and incentives and at the organisational level, partners may have their own cultures and processes. Thus, interorganisational collaboration is not necessarily a panacea, but has advantages and disadvantages. The challenges are somewhat heightened in the MedTech sector where collaborative working cuts across established professional boundaries, brings together diverse knowledge from an array of disciplines, and often disrupts existing medical practice. Given these factors, this article presents a review of the extant management literature examining the complexities within multi-party collaboration and ways to drive these partnerships forwards. The article emphasises the critical value of interpersonal relationships within collaborations and offers means of strengthening them.